A Case of Merkel Cell Carcinoma with Parotid Lymph Node Metastasis - (:unkn) unknown (My University, 1994)
We report a case of Merkel cell carcinoma with parotid lymph node metastasis. The pathology, clinical appearance and management of this rare tumor are discussed.